Ensaios de extrusão de barras entre matrizes de perfil sigmoidal - Danna, Francisco Luiz (1973)
Preliminarily, simple and plane-strain compression tests were made with pure and commercial lead in order to determine their isotropy and work-hardening conditions. Strip-extrusion experiments were afterwards made with a sigmoidal die profile for the maximum reduction condition, and with a straight die profile with the sarne reduction and axial lenght. The resul ts were compare d with those predi cted by the sigmoidal profile theory and comparisons were made between the two types of profiles. The influences on the process of work-hardening, friction and granulometry were also verified.